2012
DOI: 10.18673/gs.v3i1.24296
|View full text |Cite
|
Sign up to set email alerts
|

A Política Saúde do Homem e sua operacionalização na Atenção Primária à Saúde

Abstract: Este estudo visa refletir sobre a operacionalização da Política Saúde do Homem no cotidiano do trabalho na atenção primária à saúde, especificamente na Estratégia Saúde da Família, e discorre sobre as barreiras apontadas pelo Ministério da Saúde como limitantes da participação dos homens na atenção primária, que são a organização dos serviços e a socialização masculina. O distanciamento dos homens dos serviços da atenção primária à saúde é um dos desafios enfrentado por equipes da Estratégia Saúde da Família a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 5 publications
1
1
0
5
Order By: Relevance
“…This finding is consistent with the alarming epidemiological data about high morbidity-mortality and resistance of the male population in Brazil, seeking health services because of the disease and the search for primary care have been considered a sign of male weakness and contributes so that men, in all life cycles, are deemed invulnerable (19)(20) . Therefore, it is believed that the discussion about In fact, some adolescents showed that they considered themselves vulnerable, but the vulnerability was directed to the behaviors of their sexual partners.…”
Section: Resultssupporting
confidence: 86%
“…This finding is consistent with the alarming epidemiological data about high morbidity-mortality and resistance of the male population in Brazil, seeking health services because of the disease and the search for primary care have been considered a sign of male weakness and contributes so that men, in all life cycles, are deemed invulnerable (19)(20) . Therefore, it is believed that the discussion about In fact, some adolescents showed that they considered themselves vulnerable, but the vulnerability was directed to the behaviors of their sexual partners.…”
Section: Resultssupporting
confidence: 86%
“…The treatment of obesity had a mean cost of R$ 25,404,454.87, increasing by R$ 16,260,197.86 over the study period; diabetes had a mean cost of R$78,471,736.08, increasing by R$ 25,817,762.98 over the study period; acute myocardial infarction had a mean cost of R$197,615,477.67, increasing by R$93,673,355.73 over the study period; and hypertension had a mean cost of R$43,773,393.48, increasing by only R$1,679,789.79 over the study period. The treatment of women for all conditions cost more than that of men, except for myocardial infarction.…”
Section: Resultsmentioning
confidence: 99%
“…Um dos motivos que pode estar atrelado ao maior gasto com saúde por parte das mulheres é que, desde a década de 1980, com a implantação do Programa de Atenção Integral à Saúde da Mulher (PAISM), as mulheres foram incentivadas a procurar mais os serviços de saúde e novas especialidades surgiram para atender a esta demanda, tanto na área médica, como na farmacêutica 25 . Por outro lado, a Política Nacional de Atenção Integral à Saúde do Homem (PNAISH) foi implantada apenas em 2009, e várias cidades ainda sofrem com problemas para atender às demandas da execução e monitoramento do programa 26 .…”
Section: Sexounclassified
“…Essa forma de socialização expõem os homens a situações de risco, situação preocupante, pois deixam de lado o cuidado com a sua saúde, que é visto como demonstração de fraqueza, coisa de mulher. Na fase adulta, essa forma de lidar com a saúde traz consequências trágicas, como demonstram os números da mortalidade e morbidade masculinas (Duarte, Oliveira, Souza, 2012).…”
Section: Homem Forte X Saúde Fracaunclassified
“…O desafio, portanto é trazer os homens aos serviços de saúde de modo que os indicadores de promoção da saú-de masculina possam ser melhorados, ou seja, para que a integralidade da atenção à saúde seja alcançada englobando o público masculino como um todo (Duarte, Oliveira, Souza, 2012). Quando não reconhecemos os homens como possíveis sujeitos de cuidado, deixamos de estimulá-los às práticas de promoção e prevenção da saúde ou não reconhecemos casos em que eles demonstram tais comportamentos.…”
Section: "Homem Tem Medo De Perder O Emprego ()"-"Então Você Não unclassified